Analisis Asuransi Produk Pembiayaan Rumah Subsidi Di Pt Bank Sumut Unit Usaha Syariah - Ivanka, Meitia; Syahriza, Rahmi (Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to analyze the implementation of insurance in subsidized housing financing products at PT Bank Sumut Unit Usaha Syariah. The need for adequate and affordable housing is one of the basic needs that must be met, and the Indonesian government strives to increase access to homeownership for low-income communities through various housing subsidy programs. An important instrument in subsidized housing financing is the role of financial institutions, including Islamic banks, which provide financing products according to sharia principles. PT Bank Sumut Unit Usaha Syariah offers subsidized housing financing products designed to help low-income communities own homes easily and in accordance with sharia financial principles. This research employs a descriptive qualitative approach using a case study method, with data collected through in-depth interviews with product managers, insurance staff, and customers, as well as observations at the research location and analysis of related documents. The results indicate that insurance in subsidized housing financing products provides protection against credit risk and financial losses for both the bank and customers, increases customer trust, and facilitates the financing process. However, challenges remain, such as customers' low understanding of the benefits of insurance and the perception that the claims process is complicated.